Generalized riesz method and convergence acceleration - Tammeraid, I. (Mathematical Modelling and Analysis, 2004)
Several propositions on A‐boundedness for generalized Riesz method (5ft, Pn ), where Pn are linear bounded operators from Banach space X into X, are proved. These results are applied to study convergence acceleration using generalized Riesz method and generalized Zygmund method.Apibendrintas Riesz metodas ir konvergavimo pagreitisSantrauka. Straipsnyje įrodyta keletas teiginių, susijusių su A aprežtumu apibendrintam Rieszo metodui, kai Pn yra tiesinis aprėžtasis operatorius Banacho erdvėje X. Šie rezultatai taikomi tiriant Rieszo ir apibendrinto Zygmundo metodų konvergavimo pagreitį.First Published Online: 14 Oct 2010